Factors Related to Fabric Hygienic Mask Wearing Behaviors to Prevent COVID-19 among People in Pathumthani Province - Khorskull, Somboon (Journal of Public Health Nursing, 2021)
Wearing a fabric hygienic or cloth mask can be used to prevent the spread of the coronavirus 2019 in situations where surgical masks are scarce. This descriptive research aimed to study the factors related to cloth mask utilization behavior in COVID-19 prevention of peoples in Pathumthani Province. The study samples consisted of 315 people. Data were collected using 3 questionnaires; the demographic data record form, cloth mask behavior, and Cognitive-Perceptual factors of Pender’s health promotion model (HPM); perceived benefit, perceived barriers, self-efficacy, interpersonal influence, and situational influence. The content validity test was at 1.00, and the reliability test was conducted using Cronbach’s alpha coefficient at .80 and .85. Statistics used for data analysis consisted of Spearman’s s Correlation and Pearson’s Product Moment Correlation coefficient. The study results showed that education level and cognitive-perceptual factors including perceived benefit and situational influence were statistically significant related to cloth mask utilization behavior (r = -.157, .366 and .216 consecutively). The study results should be used as a guideline to promote the perception of benefits and the correct information of situation for cloth masks using to prevent infection.